DASAR HUKUM DAN REALITA TRAFFICKING DI INDONESIA - Ferdricka Nggeboe (Universitas Batanghari Jambi, 2011)
Passed Act No. 21 of 2007 about the eradication of criminal acts of Trafficking people gave new hope will be handling cases of trafficking that is rife in Indonesia. This crime is a serious crime, as has happened in the event against human rights, so it is not wrong to many who stated that this crime is no less dangerous than the evils ofNarcotics and illegal Weapons sales and terrorists.Basically, the criminal acts of trafficking persons, in addition to its nature as an international or transnational crimes and carried out in an organized, also are very detrimental and dangerous to the community, nation, and State so that the necessary legal provisions of a different material, for example the existence of provisions of criminal threats that are heavy for the culprit. In addition, the establishment of law No. 21 of 2007 is intended to embody the national commitment towards the desire of Nations International in eradicating the crime trade people because of acts of transnational and organized the pidananya. In an attempt to examine this matter, witnesses the victim who became one of the key disclosure of this case should be separated from the threat of violence or pressure (Fear of Crime), by providing a sense of security and protected to the victims, so that the necessary accompaniment for the victimsin the process of case examination.Crime victims are usually will experience prolonged trauma and so the need for an escort by both countries as well as the non-governmental organizations in the process of rehabilitation and reintegration with society and the environment. Likewise, awarding restitution from the offender to the victim has to be fought, given the many events in the form of this crime, the victim has been exploited, either sexually exploits, as well as physical and often are not given in Exchange for nothing. In addition to the restitution of the State should also think about compensations, because not allperpetrators of crime can provide restitution to their victims.keyword : law, reality, trafficking